Penguatan Fungsi dan Peran Sekolah: Solusi Pembelajaran Sains bagi Generasi Y dan Z di Era 4.0 - Wulandari Saputri; Panggih Priyambodo; Winarto Winarto; H. B. A. Jayawardana (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2022)
This study aims to describe science learning solutions for generations Y and Z in Era 4.0. The method used is a literature study of various previous research results. The results of the study indicate that there are several things that can be pursued in order to strengthen the role and function of schools in the 4.0 era, including strengthening the scientific approach, applying multiple intelligences approaches, involving and utilizing elements of technology in learning, implementing contextual learning, as well as strengthening the character of students. In conclusion, it is necessary to strengthen the function and role of schools in realizing relevant science learning in the 4.0 era for generation Y (millennial generation) and generation Z. Keywords: Era 4.0, Multiple Intelligences, Contextual Learning, Scientific Approach, Character Education